Corona, Theodicee en Job - G. Bosman, Frank; L.H.M. van Wieringen, Archibald (Religie & Samenleving, 2021)
Having a look at the public treatment of the corona pandemic, we can see reminiscents of the theodicy discussion in the Christian philosophical/theological tradition. The main treatments of the theodicy are Irenaean or Augustinian: either the evil was linked to some greater good, or the evil was linked to the human development. In the case of corona, both theodicies are present, although in a secular form. With the help of the book of job, the authors argue that both theodicees fail and a biblical perspective of fighting the evil (along with God) without links to scapegoats or education is more fruitful.